TINJAUAN YURIDIS KLAUSULA BAKU PADA TIKET SPEEDBOAT SINERGI CIPTA MANDIRI RUTE KOTA PONTIANAK-KAB KAYONG UTARA - NIM. A1011211136, CHANIA ELGA NINDYA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This study aims to analyze the standard clauses that occur as a result of the transportation agreement between the carrier and passengers of the Sinergi Cipta Mandiri speedboat on the Pontianak-Kayong Utara route. The formulation of the problem in this study is